Монгол хэлийг хоёрдогч хэл болгон заан сургаж ирсэн арга туршлага, цаашдын төлөв: The Previous Methodology and Experience on Teaching the Mongolian as a Second Language and its Perspective - Ch., Battulga; B., Bayartuul (Mongolian Journal of Foreign Languages and Cultures, 2023)
The National University of Mongolia plays an important role in protecting, developing, and disseminating Mongolian language and culture in the world. The Government of Mongolia has intensely supported teaching Mongolian as a second language and included a specific article in the “Vision- 2025”-long term policy document approved by the Parliament. Therefore, the strategy, curriculum, and methodology on teaching Mongolian language require to be updated and developed. As the number of people interested in Mongolia growing year by year, the need to learn Mongolian as a second language is also increasing. In this article, we aimed to discuss the importance of establishing a Mongolian language training center shortly.